Research progress on flat epithelium of the inner ear - He, L; Guo, J-Y; Liu, K; Wang, G-P; Gong, S-S (Physiological research, 2020)
Sensorineural hearing loss and vertigo, resulting from lesions in the sensory epithelium of the inner ear, have a high incidence worldwide. The sensory epithelium of the inner ear may exhibit extreme degeneration and is transformed to flat epithelium (FE) in humans and mice with profound sensorineural hearing loss and/or vertigo. Various factors, including ototoxic drugs, noise exposure, aging, and genetic defects, can induce FE. Both hair cells and supporting cells are severely damaged in FE, and the normal cytoarchitecture of the sensory epithelium is replaced by a monolayer of very thin, flat cells of irregular contour. The pathophysiologic mechanism of FE is unclear but involves robust cell division. The cellular origin of flat cells in FE is heterogeneous; they may be transformed from supporting cells that have lost some features of supporting cells (dedifferentiation) or may have migrated from the flanking region. The epithelial-mesenchymal transition may play an important role in this process. The treatment of FE is challenging given the severe degeneration and loss of both hair cells and supporting cells. Cochlear implant or vestibular prosthesis implantation, gene therapy, and stem cell therapy show promise for the treatment of FE, although many challenges remain to be overcome.
Keywords: Ear, Inner; epitelo-mezenchymální tranzice; Epithelial-Mesenchymal Transition; Animals; lidé; epitel; vnitřní vláskové buňky; Hair Cells, Auditory, Inner; Hearing Loss, Sensorineural; Noise; hluk; Epithelium; Humans; zvířata; vnitřní ucho; percepční nedoslýchavost